Granulosa cell endothelin-2 expression is fundamental for ovulatory follicle rupture - Joseph A. Cacioppo (Nature Portfolio, 2017)
Abstract Ovulation is dependent upon numerous factors mediating follicular growth, vascularization, and ultimately oocyte release via follicle rupture. Endothelin-2 (EDN2) is a potent vasoconstrictor that is transiently produced prior to follicle rupture by granulosa cells of periovulatory follicles and induces ovarian contraction. To determine the role of Edn2 expression, surgical transplant and novel conditional knockout mice were super-ovulated and analyzed. Conditional knockout mice utilized a new iCre driven by the Esr2 promoter to selectively remove Edn2. Follicle rupture and fertility were significantly impaired in the absence of ovarian Edn2 expression. When ovaries of Edn2KO mice were transplanted in wild type recipients, significantly more corpora lutea containing un-ovulated oocytes were present after hormonal stimulation (1.0 vs. 5.4, p = 0.010). Following selective ablation of Edn2 in granulosa cells, Esr2-Edn2KO dams had reduced oocytes ovulated (3.8 vs. 16.4 oocytes/ovary) and smaller litters (4.29 ± l.02 vs. 8.50 pups/dam). However, the number of pregnancies per pairing was not different and the reproductive axis remained intact. Esr2-Edn2KO ovaries had a higher percentage of antral follicles and fewer corpora lutea; follicles progressed to the antral stage but many were unable to rupture. Conditional loss of endothelin receptor A in granulosa cells also decreased ovulation but did not affect fecundity. These data demonstrate that EDN2-induced intraovarian contraction is a critical trigger of normal ovulation and subsequent fecundity.